All Days 2009
DOI: 10.2118/124783-ms
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Depth of Penetration of Downhole Perforators

Abstract: Productivity of a cased-and-perforated well depends on completion parameters (charge, shot density and phasing), formation properties (lithology, anisotropy, permeability, fluid properties and saturations), and environmental conditions (pressure and temperature). A shaped charge produces a jet of dense, typically solid material traveling at very high velocity which penetrates casing, cement, and formation. This penetration process creates a tunnel in the rock connecting the reservoir and the wellbore. Stress w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Other researchers (i.e. [18]) have come to similar conclusions. The fact that alternative penetration models have recently been introduced ([20]) is further testimony to the industry-recognized need for improvements over the conventional models.…”
Section: The Need For Improved Modelssupporting
confidence: 66%
See 1 more Smart Citation
“…Other researchers (i.e. [18]) have come to similar conclusions. The fact that alternative penetration models have recently been introduced ([20]) is further testimony to the industry-recognized need for improvements over the conventional models.…”
Section: The Need For Improved Modelssupporting
confidence: 66%
“…1) API Section I concrete Berea sandstone (normalized to 7000 psi UCS) 2) Berea rock of different UCS (rock strength effect) 3) Unstressed rock stressed rock (influence of effective stress) 4) Effects of cement, casing, and wellbore fluid Recent surveys [17,18] have summarized some of these historical correlations.…”
Section: A Brief History Of Conventional Penetration Modelsmentioning
confidence: 99%
“…1997, Brooks et al 2011 to study perforation systems and their flow effectiveness in more detail (using API-RP 19B Section II and IV). A perforating flow laboratory can be a valuable engineering simulation tool to provide insight into the following: -Perforation tunnel geometry (shape, penetration, damaged zones, hole size) (Brooks et al 2011) -Damaged zone around the perforation tunnel -Tunnel cleanup mechanisms -Underbalance optimization (Walton et al 2001, Manalu et al 2005) -Productivity analysis (Halleck 1997) -Development and validation of numerical models (Sun et al 2012, Sun et al 2013, Gladkikh et al 2009) -Selection of gun systems -Deployment techniques Reduction and management of perforating debris (in particular, charge case debris) is a critical aspect that determines the success of a perforating job in complex well completions. It is well known that steel and zinc-case charges are commonly used shaped charges for perforating, with the zinc case charge being the low-debris option as it yields smaller (powdered) debris which can easily be flowed back, and is acid soluble, avoiding significant operational issues that often result from the larger debris of steel cases.…”
Section: Introductionmentioning
confidence: 99%
“…First perforation devices that employ a bullet as a shooting tool for breaking the rock, were replaced by shaped charge perforation around 50 year ago (Gladkikh 2009). This new device has continuously been developed during this period by experimental studies which showed that many factors including the formation porosity (Behrmann and Halleck 1988a), ultimate strength (Thompson 1962;Behrmann and Halleck 1988a;Behrmann et al 1992;Ott et al 1994), acoustic velocities and bulk modulus (Venghiattis 1963;Halleck et al 1988;Halleck et al 1991), grain size (Brooks et al 1998), lithology (Aseltine 1985;Halleck et al 1991;Smith et al 1997;Halleck et al 2004;Snider et al 2006), fluid type, saturation, and pore pressure (Aseltine 1985;Behrmann and Halleck 1988b;Halleck et al 1988;Bird and Block 1996;Karacan et al 2001 ;Grove et al 2008), heterogeneity (Smith et al 1997), confining and effective stresses (Saucier and Lands 1978;Halleck et al 1988;Henderson and Navarette 1990;Ott et al 1994;Grove et al 2008), and wellbore pressure (Behrmann and Halleck 1988b) are the important parameters affecting the perforation quality.…”
Section: Introductionmentioning
confidence: 99%